Risk Perception and COVID-19 During Lockdown: Evidence from an Italian Sample - Marchesi, Andrea; De Luigi, Nicola (Italian Sociological Review, 2022)
This paper investigates how a specific extraordinary event such as the COVID-19 pandemic is perceived among individuals. Upsetting the taken-for-granted practices of people’s everyday life, the pandemic caused negative emotional responses, mainly the feeling of concern about its aftermath on health and social and economic aspects. However, these responses are not equally spread among social groups. Some of them are more associated with states of panic and anxiety, according to their socially defined and transmitted roles and identities. This paper focuses on a specific element of the perception of the COVID-19 pandemic, i.e. risk, based on a survey conducted in Italy (N = 1,704) during the last three weeks of lockdown (26th of April 2020 – 17th of May 2020). The analyses aim to detect patterns in socio-demographic variables in COVID-19 risk perception in the Italian population during lockdown, also accounting for their variation over time. In fact, the analyses suggest that approaching and being aware of the loosening of lockdown measures (18th of May 2020) may have decreased the perceived risk. Results prove consistent with findings from previous research.